Safety attitudes culture remain stable in a transplant center: evidence from the coronavirus pandemic - Zhang, Chi; Wilson-Sheehan, Sena; Ruch, Brianna; Wagler, Josiah; Abidali, Ali; Lim, Elisabeth S.; Chang, Yu-Hui; Fowler, Christopher; Douglas, David D.; Mathur, Amit K. (Frontiers in Transplantation, 2023)
We sought to understand how safety culture may evolve during disruption, by using the COVID pandemic as an example, to identify vulnerabilities in the system that could impact patient outcomes. A cross-sectional analysis of transplant personnel at a high-volume transplant center was conducted using the Safety Attitudes Questionnaire (SAQ). Survey responses were scaled and evaluated pre-and intra-COVID (2019 and 2021). Two-hundred and thirty-eight responses were collected (134 pre-pandemic and 104 intra-pandemic). Represented organ groups included: kidney (N=89;38%), heart (N=18;8%), liver (N=54;23%), multiple (N=66;28%), and other (N=10;4%). Responders primarily included nurses (N=75;34%), administration (N=50;23%), and physicians (N=24;11%). Workers had high safety, job satisfaction, stress recognition, and working conditions satisfaction (score ≥75) both before and during the pandemic with overlapping responses across both timepoints. Stress recognition, safety, and working conditions improved intra-COVID, but teamwork, job satisfaction, and perceptions of management were somewhat negatively impacted (all p>0.05). Despite the serious health care disruptions induced by the pandemic, high domain ratings were notable and largely maintained in a high-volume transplant center. The SAQ is a valuable tool for healthcare units and can be used in longitudinal assessments of transplant culture of safety as a component of quality assurance and performance improvement initiatives.